Artemisinin-resistant malaria and a prevention strategy - Francis M Malwal (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2020)
Malaria is a widely spread infectious disease and claims many lives annually in the African region. Therefore, prevention and effective therapy are significantly crucial for the successful reduction of malaria morbidity and mortality. However, recently emerging artemisinin-resistant parasites in Southeast Asia, South America, and Rwanda have raised concern globally. Studies have established that artemisinin-resistant is associated with a mutation in the Kelch13 (K13) propeller domain of malaria parasites. This mutation delays malaria parasite clearance from the bloodstream to more than three days following ACT's therapy. The objective of this paper is to alert authorities and researchers to the upcoming threat of artemisinin-resistant and recommend prevention strategies. Health authorities need to invest more in malaria prevention, enforcing existing laws, monitoring emerging resistance, and its impacts. Moreover, healthcare professionals can play a vital role by adhering to malaria treatment guidelines, avoiding monotherapy, and promoting antimalarial adherence